Modeling hyperpolarized lactate signal dynamics in cells, patient‐derived tissue slice cultures and murine models. (7th January 2021) - Ahamed, Fayyaz; Van Criekinge, Mark; Wang, Zhen J.; Kurhanewicz, John; Larson, Peder; Sriram, Renuka
Abstract : Determining the aggressiveness of renal cell carcinoma (RCC) noninvasively is a critical part of the diagnostic workup for treating this disease that kills more than 15, 000 people annually in the USA. Recently, we have shown that not only the amount of lactate produced, as a consequence of the Warburg effect, but also its efflux out of the cell, is a critical marker of RCC aggressiveness and differentiating RCCs from benign renal tumors. Enzymatic conversions can now be measured in situ with hyperpolarized (HP) 13 C magnetic resonance (MR) on a sub‐minute time scale. Using RCC models, we have shown that this technology can interrogate in real time both lactate production and compartmentalization, which are associated with tumor aggressiveness. The dynamic HP MR data have enabled us to robustly characterize parameters that have been elusive to measure directly in intact living cells and murine tumors thus far. Specifically, we were able to measure the same intracellular lactate longitudinal relaxation time in three RCC cell lines of 16.42 s, and lactate efflux rate ranging from 0.14 to 0.8 s −1 in the least to the most aggressive RCC cell lines and correlate it to monocarboxylate transporter isoform 4 expression. We also analyzed dynamic HP lactate and pyruvate data from orthotopic murine RCC tumors using a simplified one‐compartment model, and showed comparable apparent pyruvate to lactate conversion rate ( k PL ) values with those measured in vitro. This kinetic modeling was then extended to characterize the lactate dynamics in patient‐derived living RCC tissue slices; and even without direct measurement of the extracellular lactate signal the efflux parameter was still assessed and was distinct between the benign renal tumors and RCCs. Across all these preclinical models, the rate parameters of k PL and lactate efflux correlated to cancer aggressiveness, demonstrating the validity of our modeling approach for noninvasive assessment of RCC aggressiveness. Abstract : Kinetic modeling of 13 C hyperpolarized pyruvate, intracellular and extracellular lactate signals from renal cell carcinoma (RCC) cell lines in a bioreactor allowed for noninvasive assessment of intracellular lactate longitudinal relaxation time and the k PL and k LEfflux kinetic rate parameters, which represent LDH activity and MCT4 expression, respectively. The calculated k PL and k LEfflux values in various cell lines followed expected trends and k PL results in patient‐derived tissue slices and an orthotopic murine model of RCC recapitulated in vitro results.